John and the hole [videorecording (DVD)] - Giacobone, Nicolás; Shotwell, Charlie; Hall, Michael C., 1971-; Ehle, Jennifer, 1969-; Farmiga, Taissa, 1994- (IFC Films, 2022)
A coming-of-age psychological thriller that plays out the unsettling reality of a kid who holds his family captive in a hole in the ground.